(untitled) (Student’s Journal of Health Research Africa, 2024)
Objective This study aims to assess the effectiveness and safety of the Harmonic scalpel compared to electrocautery for dissecting and controlling bleeding in the gallbladder during laparoscopic cholecystectomy. Methods 300 patients underwent laparoscopic cholecystectomy, following strict selection criteria. These criteria included having chronic cholecystitis, no complaints at the time of operation, being between the ages of 18 to 70 years, having a normal body weight, an American Score of Anesthesia (ASA) classification of 1 or 2, no prior upper abdominal surgeries, and a gall bladder wall thickness of less than 6 mm as determined by preoperative ultrasonography. Results The study encompassed a total of 300 patients, with 155 patients assigned to the first group receiving electrocautery and 145 patients assigned to the second group receiving harmonic treatment. Intraoperative hemorrhage was observed in a total of 32 cases within the initial group, while the subsequent group exhibited 15 cases of intraoperative hemorrhage. A total of 24 patients in the electrocautery group exhibited gallbladder perforation, whereas slipped stone incidents were recorded in 10 patients. In comparison, within the harmonic group, 11 patients experienced gallbladder perforation and 2 patients encountered slipped stone incidents. Conclusion The harmonic scalpel has demonstrated notable safety and efficacy as a surgical instrument to dissect the gall bladder and achieve hemostasis during laparoscopic cholecystectomy. If the harmonic scalpel is accessible within the operation theatre, it can serve as a suitable alternative to electrocautery for these specific procedures. Recommendation The choice between the Harmonic scalpel and electrocautery should be made on a case-by-case basis, taking into consideration the surgeon’s experience, patient factors, and specific clinical requirements.